Sala de Recuperação da Beleza: Sentidos sobre o belo em um corpo de transição - Federizzi, Andressa Almeida (2018)
The present research focused on reflections and analyzes under the concepts of French Discourse Analysis, seeking to understand the discursive processes that surround the beautiful female body of South Korea, modified through surgical intervention, and that allow the production of meaning effects. Through the analysis of the photographs of the project Beauty Recovery Room by Ji Yeo published in the magazine Marie Claire in 2014, and in the discursive sequences of O Globo.com, Hypeness, Marie Claire magazine and BBC Brazil Portal on the project and plastic surgery in South Korea can be affirmed that there is the functioning of the language and the ideology acting on the subjects and their bodies. Thus, the body of the photograph reproduces Discursive Formations (of appreciation of the beautiful), Imaginary Formations (of the body of the magazine) and mainly, Ideological Formations (capitalist logic) in which feminine beauty, plastic surgery and consumption are interconnected, conferring subject the right / duty to modify their body based on social determinations that dictate the place that the female body should occupy under contemporary values in South Korean society. There is therefore a body in transition, in motion, in improvement, aiming at the "satisfaction" that the beautiful body offers as if capable of providing welfare, happiness, success and completeness to the desiring subject.